Parents’ Language Beliefs and Attitudes toward the Indonesian Language in Transnational Families - Syafruddin, Yuliana Angreini; Yoestara, Marisa; A'la, Putri Nurul (Universitas Teuku Umar, 2025)
Parents’ language beliefs and attitudes play a significant role in shaping language practices at home. This descriptive qualitative study focuses on the families’ perspectives on multilingualism and their views on the necessity of learning the Indonesian language in order to find out parents’ beliefs and attitudes toward the Indonesian language. In collecting the data, this study used semi-structured interviews with 11 Indonesian-Australian families in Melbourne. The collected data were subsequently analyzed by using NVivo software. The findings indicate that all parents support multilingualism, recognizing its cognitive benefits, economic advantages, and the influence of their own multilingual experiences. However, variations exist regarding the inclusion of the Indonesian language in their children's multilingual repertoire. While eight families emphasized the importance of learning Indonesian to maintain family bonds and cultural heritage, three families perceived it as unnecessary due to their children’s primary identity as Australian citizens, infrequent visits to Indonesia, and the limited global utility of the language. These findings suggest that while multilingualism is believed to be widely valued, parental attitudes toward specific languages are influenced by their personal experiences, perceived utility, and cultural connections. Further research into how these beliefs translate into actual language practices at home would provide deeper insights into family language management.